2018
DOI: 10.4103/ijccm.ijccm_365_17
|View full text |Cite
|
Sign up to set email alerts
|

A prospective antibacterial utilization study in pediatric intensive care unit of a tertiary referral center

Abstract: Purpose:Antibacterials are commonly prescribed to Pediatric Intensive Care Unit (PICU) patients. However, inappropriate antibacterial prescriptions lead to increases in antibacterial resistance, treatment cost, duration of treatment, and poor clinical outcome. The antibacterial utilization study assesses the prescription patterns and if necessary recommends the interventions to improve antibacterial prescriptions. Hence, the present prospective groundwork was conducted.Materials and Methods:The study was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…This study revealed the mean duration of antibiotic therapy as 5.90 days ± 3 days with similarities observed with Mali et al [ 27 ] (6.08 days±6.27 days).…”
Section: Discussionsupporting
confidence: 89%
“…This study revealed the mean duration of antibiotic therapy as 5.90 days ± 3 days with similarities observed with Mali et al [ 27 ] (6.08 days±6.27 days).…”
Section: Discussionsupporting
confidence: 89%
“…Irrespective of age group, most of the drugs were administered parenterally followed by the oral route ( Table 3). The median (IQR) for the total number of drugs per encounter was significantly different (P = 0.0001) between adult, paediatric and neonatal ICUs: 11 (8)(9)(10)(11)(12)(13)(14)(15)(16)…”
Section: Classes Of Drugs Administered In the Study Populationmentioning
confidence: 99%
“…Children and neonates are prone to adverse drug reactions considering the developmental changes in their organs, and most of these drugs have not been tested in this subpopulation. In a recent study from the paediatric ICU of a developing country, almost 98% received at least one antimicrobial, of which ceftriaxone was the most administered [ 9 ]. A recent systematic review of drug utilisation studies (DUS) in critically ill neonates revealed that they had been carried out only in a few countries such as Brazil ( n = 1), the EU ( n = 7), India ( n = 5), Iran ( n = 1) and the USA ( n = 6) [ 10 ].…”
mentioning
confidence: 99%
“…Antimicrobials use amongst them should receive special attention as they are prone to increased risk of exposure to resistant strains in the later stages of their life. 5 Currently there is global increase in AMR and considerable shortfalls in the development and availability of new antimicrobials. Therefore, implementing measures to maintain the usefulness of existing antimicrobial agents has become a top public health concern.…”
Section: Introductionmentioning
confidence: 99%